1998
DOI: 10.1007/s004420050618
|View full text |Cite
|
Sign up to set email alerts
|

Solar ultraviolet-B radiation affects plant-insect interactions in a natural ecosystem of Tierra del Fuego (southern Argentina)

Abstract: We examined the effects of solar ultraviolet-B radiation (UVB) on plant-herbivore interactions in native ecosystems of the Tierra del Fuego National Park (southern Argentina), an area of the globe that is frequently under the Antarctic "ozone hole" in early spring. We found that filtering out solar UVB from the sunlight received by naturally-occurring plants of Gunnera magellanica, a creeping perennial herb, significantly increased the number of leaf lesions caused by chewing insects. Field surveys suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
87
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 37 publications
7
87
0
1
Order By: Relevance
“…G. magellanica is one of the first species to resume growth at the end of the winter in the southern part of Tierra del Fuego. Our previous work in the National Park shows that, during early spring, G. magellanica leaf area expansion is inhibited by solar UVB (13). Therefore, in the spring of 1997, we collected leaf samples to investigate whether the spikes of solar UV that are commonly observed during ozone-hole days (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…G. magellanica is one of the first species to resume growth at the end of the winter in the southern part of Tierra del Fuego. Our previous work in the National Park shows that, during early spring, G. magellanica leaf area expansion is inhibited by solar UVB (13). Therefore, in the spring of 1997, we collected leaf samples to investigate whether the spikes of solar UV that are commonly observed during ozone-hole days (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We selected a field site in the Tierra del Fuego National Park, which is covered by Nothofagus spp. forests and has extensive bogs, scrublands, and heathlands (13)(14)(15). In the spring of 1996, we marked 20 permanent plots to study the long-term responses to partial UVB exclusion of a scrub ecosystem near Laguna Negra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A much larger impact of solar UV-B has been documented for plant-herbivore interactions. Field experiments in a broad spectrum of ecosystems show that the intensity of insect herbivory frequently increases when the UV-B component of solar radiation is experimentally attenuated using filters (Bothwell et al, 1994;Ballaré et al, 1996;Rousseaux et al, 1998;Mazza et al, 1999b;Zavala et al, 2001). In some cases, at least part of this effect of solar UV-B could be attributed to direct behavioral responses of insects to UV-B photons (Mazza et al, 2002).…”
mentioning
confidence: 99%
“…However, insect growth and choice bioassays have demonstrated that UV-B effects on herbivory are in many cases indirect; i.e. mediated by UV-B-induced changes in plant tissues, which in turn affect insect feeding behavior and growth performance (Ballaré et al, 1996;Rousseaux et al, 1998;Mazza et al, 1999b;Zavala et al, 2001). The nature of these changes is unknown.…”
mentioning
confidence: 99%